Postmodern, feminist and postcolonial currents in contemporary Japanese culture : a reading of Murakami Haruki, Yoshimoto Banana, Yoshimoto Takaaki and Karatani Kōjin - Murakami, Fuminobu, 1951- (Routledge/Asian Studies Association of Australia East Asia series (2005), 2005)
Using the Euro-American theoretical framework of postmodernism, feminism and post-colonialism, this book analyses the fictional and critical work of four contemporary Japanese writers; Murakami Haruki, Yoshimoto Banana, Yoshimoto Takaaki and Karatani Kojin. In addition the author reconsiders this Euro-American theory by looking back on it from the perspective of Japanese literary work. Presenting outstanding analysis of Japanese intellectuals and writers who have received little attention in the West, the book also includes an extensive and comprehensive bibliography making it.